Plant cutting, gathering, conveying processes and equipment - Skachkov, R. N. (ТДАТУ, 2021)
The combine harvesters have row crop corn headers for harvesting from 6 to 24 rows at the same time. The rollers with knives and cross blades cut off the stalks while being pulled down. Such the stalk roller with knives is made of a shaft, helical spirals, radial multi-blades and four longitudinal knives.
Keywords: seed harvesters; plant cutting; stalk roller with knives